Faktor-Faktor Yang Mempengaruhi Kebijakan Hutang Dengan Profitabilitas Sebagai Pemoderasi - Giovanni Angeline, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to know the influence of dividends, company assets, company size and growth on debt policy selection decisions that should be taken by the companies listed on the IDX in period of 2017-2019. The sample selection was done by using the purposive sampling method and some secondary data as many as 182 companies with 37 sample. Processing data in this study is using a Moderated Regression Analysis (MRA), which was carried out with the 11th version of the E-views application and with the support from Michrosoft Office 365. The results obtained show that dividend policy and profitability have a significant effect on company debt policy, while asset structure, size and growth the company does not have a significant effect on debt policy. Profitability is significantly moderates the relationship between dividend policy and debt policy, but cannot moderates or un-significant or weaken the relationship of other independent variable with debt policy. The implication of this research is the need to increase the use of good debt in order not to experience excess internal funds and excess use of external funds, in order to avoid agency problems and agency costs that arise.